2021
DOI: 10.3390/chemosensors9050095
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Inkjet-Printed Temperature Sensors on Paper Substrate for the Integration into Natural Fiber-Reinforced Lightweight Components

Abstract: In a unique approach to develop a “green” solution for in-situ monitoring, low-cost inkjet-printed temperature sensors on paper substrate were fully integrated into natural fiber-reinforced lightweight components for which structural health monitoring is becoming increasingly important. The results showed that the sensors remained functional after the vacuum infusion process; furthermore, the integration of the sensors improved the mechanical integrity and stability of the lightweight parts, as demonstrated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
(52 reference statements)
0
8
0
Order By: Relevance
“…With improved selection of materials and manufacturing parameters, researchers were able to tune the nanoparticle structures towards the property of bulk silver. The range of TCR of printed silver nanoparticle temperature sensors in the literature varies between 0.6 × 10 −3 K −1 and 2.8 × 10 −3 K −1 [ 2 , 9 , 10 , 11 , 12 , 13 , 14 ]. The properties of silver nanoparticle sensors are documented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With improved selection of materials and manufacturing parameters, researchers were able to tune the nanoparticle structures towards the property of bulk silver. The range of TCR of printed silver nanoparticle temperature sensors in the literature varies between 0.6 × 10 −3 K −1 and 2.8 × 10 −3 K −1 [ 2 , 9 , 10 , 11 , 12 , 13 , 14 ]. The properties of silver nanoparticle sensors are documented in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…At a temperature of 60 °C, the influence of the increased humidity was 0.26%, which equals an error of 1.64 °C. Non-encapsulated sensors showed an increase of 10% due to the humidity variation, which shows that an encapsulation is a great option to reduce such cross-influences [ 9 ]. Mutee ur Rehman investigated the encapsulation of printed PEDOT:PSS temperature sensors with an Al 2 O 3 layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper‐based biface multi‐sensor tag could be of particular importance in lightweight construction and in the case of natural fiber‐reinforced composite materials, due to its sustainable fabrication. Although previous work has shown that the integration of paper‐based sensors per se does not negatively affect the mechanical integrity of lightweight elements, [ 5 ] but the 3D geometry of the packaged chip could. To counteract this, bare dies or even ultra‐thinned chips [ 33 ] could be employed.…”
Section: Discussionmentioning
confidence: 99%
“…These devices can also provide qualitative or quantitative results and data at the point of care without the need for specialized equipment or power sources. Several paper-based devices have been developed for various applications, such as for water analysis [1][2][3][4], biomedical applications [5,6], food analysis [7][8][9][10], soil analysis [11] and many other miscellaneous applications [12][13][14][15]. The field of paper-based microfluidics is expected to continue garnering greater attention as more applications are sought after or the performance improved for the ones already developed [16].…”
Section: Introductionmentioning
confidence: 99%